The Potential Effect of Chinese Herbal Formula Hongqijiangzhi Fang in Improving NAFLD: Focusing on NLRP3 Inflammasome and Gut Microbiota. (21st February 2018) - Liang, Shu; Zhang, Yupei; Deng, Yuanjun; He, Yifang; Liang, Yinji; Liang, Zien; Chen, Yanning; Tang, Kairui; Chen, Runsen; Yang, Qinhe
Abstract : The present study investigates the potential therapeutic mechanism underlying the effects of the Chinese herbal formula Hongqijiangzhi Fang (HJF) on nonalcoholic fatty liver disease (NAFLD) in rats. Male Sprague Dawley (SD) rats were randomly divided into 4 groups (n = 8 ): control group was fed a normal diet, three other groups were fed high-fat diets (HFD), and the two treatment groups were intragastrically given a compound probiotic or HJF during the molding time. After 16 w, related indices were detected. The results showed that HJF significantly reduced abdominal aorta serum cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL), IL-1 β, and IL-18, portal venous serum lipopolysaccharide (LPS), and liver TC and TG levels in HFD-fed rats. HJF ameliorated hepatic steatosis in the liver and improved the intestinal barrier in HFD-fed rats. Activation of the NLRP3 inflammasome was reduced by HJF in HFD-fed rats. Additionally, the abundances of A. muciniphila (Verrucomicrobiaceae), F. rappini (Helicobacteraceae), and Enterobacteriaceae bacteria significantly decreased in HJF-treated HFD-fed rats. In conclusion, these result suggested that the Chinese herbal formula HJF reduced hepatic steatosis maybe through decreasing certain gut bacteria (such as Enterobacteriaceae bacteria and F. rappini ), alleviating intestinal endotoxemia and reducing NLRP3 inflammasome activation.